CRABS AND SHRIMPS - Jongkar, Grinang (UNIMAS Publisher and Natural History Publications (Borneo) Sdn. Bhd., 2023)
Research on decapod crustaceans of Sarawak dates back to the Brooke era and continued during the Japanese occupation of the State. Nonetheless, the fauna of Bako has not received as much attention as the Santubong region and Sarawak River. The reasons may be due to the relatively isolated location of the Bako Peninsula, being further from Rajah Brooke’s administrative centre (present day Kuching City), the more complex logistical requirements for a cruise along the seasonally rough seas off the rocky coastline, and the risk of pirate attack.